Mobile Application for Vehicle Maintenance and Scheduling System - Ballia, Nur Qamarina Balqis; Aimi Syamimi Ab Ghafar (Progress in Engineering Application and Technology, 2026)
Vehicle maintenance is essential to ensure reliable performance, reduce the risk of breakdowns and extend the lifespan of the vehicle. Traditional maintenance practices often rely on manual tracking and delayed diagnostic, which can lead to missed service intervals and unexpected issues. This project proposes the enhanced of an integrated system that combines real-time battery and mileage monitoring with intelligent maintenance scheduling through a mobile application. The system utilizes an ESP32 microcontroller and an OBD-II adapter to continuously collect vehicle battery and mileage data. The data is transmitted to a user-friendly android application and developed using MIT App Inventor via Bluetooth. The app tracks odometer readings and calculates a maintenance schedule based on the type of engine oil used and driving patterns. In addition, the application provides automatic service alerts also the system is designs to be low cost, efficient and scalable offering vehicle owners a smart accessible tool for proactive vehicle health management. Performance evaluation confirms the accuracy of the sensor data and the reliability of service reminders, making this solution both practical and effective for everyday use.